Proceedings of the International Conference on Quality Financial Reporting and Corporate Governance : building public trust, integrity and accountability, 28-29 July 2003, Kuala Lumpur - International Conference on Quality Financial Reporting and Corporate Governance (2003 : Kuala Lumpur) ([S.l. : s.n.], 2003)
36